The fading birth practice: urban Malay mothers in Malaysian negotiating confinement practice - Syed Hussien, Sh Fatimah Alzahrah (IIUM Press, 2019)
Malay mothers’ postpartum experiences often include a period of confinement, similar to other Asian parallel practices of “doing the month”. This confinement period comprisesof a set of beliefs, rules, and practices based on traditional eastern medicinal knowledge. Cultural practices of postpartum confinement, or berpantang, among urban mothers in Malaysiais competingwith modern western medicine in the contemporary setting.The data for this presentation is from a phenomenological study utilising twelve open-ended interviews of couples and two focus group discussions with mothers on their experience of berpantang. Even though it is still widely performed, the elements withinberpantang are handpicked by these mothers. According to these mothers, the traditional practices are thought to be inadequateor inferiorwhen compared to the authority of western biomedicine. In events where medical practitioners give opposing advice, all mothers choseto adhere to, and acceptbiomedicine’s explanations and justifications over the traditional practice. The former cultural figure head, the bidan (midwife), is no longer a part of the birthing process in these urban settings. Urban mothers today rely on or refer to their maternal mothers for knowledge and guidance on berpantang. Urban mothers who practise berpantang describe the main reason for their practise was to maintain familial peace. This paper seeks to highlightsocial and cultural implications this hegemony has particularly on challenging the continuity in the chain of traditional knowledge.